2016
DOI: 10.1002/hep.28518
|View full text |Cite
|
Sign up to set email alerts
|

Hyperhomocysteinemia activates the aryl hydrocarbon receptor/CD36 pathway to promote hepatic steatosis in mice

Abstract: Hyperhomocysteinemia (HHcy) is associated with liver diseases such as fatty liver and hepatic fibrosis; however, the underlying mechanism is still largely unknown. The current study aimed to explore the signaling pathway involved in HHcyinduced hepatic steatosis (HS). C57BL/6 mice were fed a high-methionine diet (HMD) for 4 and 8 weeks to establish the HHcy mouse model. Compared to a chow diet, the HMD induced hepatic steatosis and elevated hepatic expression of CD36, a fatty acid transport protein. The increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 44 publications
2
58
0
1
Order By: Relevance
“…HepG2 cells were treated with 100 μ m Hcy for various times (0–48 h). Consistent with previous studies , oil red O staining revealed that Hcy induced lipid droplet accumulation in HepG2 cells (Fig. A).…”
Section: Resultssupporting
confidence: 92%
“…HepG2 cells were treated with 100 μ m Hcy for various times (0–48 h). Consistent with previous studies , oil red O staining revealed that Hcy induced lipid droplet accumulation in HepG2 cells (Fig. A).…”
Section: Resultssupporting
confidence: 92%
“…The response to TCDD and related compounds is well conserved, 7,10,20 characterized by increased lipid uptake, 10,14,16 and the repression of β -oxidation 10 and de novo FA synthesis. 10,17,20 To further evaluate TCDD-elicited steatosis and progression to steatohepatitis with fibrosis, untargeted lipidomic data were integrated with complementary RNA-Seq and ChIP-Seq data sets.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 For example, ceramides promote oxidative stress and inflammation which contribute to T2D and MetS development. 13 TCDD induces hepatic lipid accumulation, mediated at least in part by the induction of the lipid transporter CD36, 10,14 and characterized by increased dietary mono- and polyunsaturated fatty acid levels. 15,16 Although previous studies suggest hepatic lipid composition is altered by TCDD, 1518 few have examined changes across lipid classes including effects on cholesterol esters and phospholipids.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, elevated homocysteine may conversely promote the progression of liver damage. Indeed, Yao et al [23] recently found that hyperhomocysteinemia could promote hepatic steatosis in mice through activation of the aryl hydrocarbon receptor/CD36 pathway. According to several experimental studies, hepatic lipid accumulation was induced in different models of hyperhomocysteinemia [2426].…”
Section: Discussionmentioning
confidence: 99%